Impactos ambientais, sociais e econômicos da utilização do sistema água viva no projeto de assentamento Monte Alegre I - Upanema-RN: os olhares das técnicas e agricultoras - Gomes, Isadora Cristina Mendes (2018)
This research emerged from the need to focus efforts to overcome the paradigm that considers that development is only linked to economic growth based on the intensive use of conventional technology, which has made invisible diverse knowledge and practices throughout history. Focusing mainly on the foundations of Sustainability, Social Technology, and Human Coexistence with the Semi-Arid and seeking to present the contributions, resistances and alternatives performed by women in this sense, a case study of an applied nature was did with the objective of knowing the environmental, social and economic impacts of using Água Viva’s System at Monte Alegre I Settlement Project - Upanema/RN from the perspective of female technicians and women farmers. This system is a gray water reuse social technology that captures the water to be reclaimed which is filtered through to be released for use in backyards and was built in an effort by entities and a group of women farmers. To achieve the proposed, the data collection was performed through exploratory, documental and bibliographic research, direct observation, semi and non structured interviews with the subjects involved, having a qualitative approach, which was based on categorization and content analysis to investigate the data. The understanding of the data in the light of bibliographical references and female subjects's speeches showed the Água Viva System contributed positively to the issue of the elimination of pollutant residues and that the cultivation and breeding practices were altered after using the system. The analysis also showed that: the local women self-organization is a central factor in the processes related to the design, construction, use and maintenance of social technology in the place; that these processes strengthen the women autonomy and are seen by women farmers and technicians as something that made possible several apprentices, although women farmers do not see themselves as thinking about technology; and that the women farmers assimilate more sharply the monetary impact of their production when they register the data regarding their production, self-consumption and exchanges. From these results, the work points to the need and importance to think about and collectively construct alternatives of human coexistence with the semi-arid that can alter the relations between the subjects themselves and those with the environment. Going further, it is evident that it is urgent to think about the life sustainability from the creation and maintenance of material or immaterial conditions that are directly related to the survival of nature, propitiating a valuation of common goods and a socialization of the tasks of the care, considering the reality of groups located under the triple dimension of gender, class and race.